Accuracy analysis and optimization of infrared guidance test device. (June 2020) - Wang, Zhou; Chen, Yin; Wang, Tao; Zhang, Bo
As an important modern weapon, the development of infrared-guided missile reflects comprehensive national strength of a country. Therefore, it is especially important to establish a semi-physical simulation device to test the performance of missile, and the test device requires high accuracy. Based on the above background, an infrared guidance test device is designed in this article. The accuracy of its shell and rotating mechanism are studied in detail, and the error factors are quantified to provide theoretical basis for structural optimization. The orthogonal experiment design reduces the number of sensitivity analysis experiments on key design parameters. Factors affecting the maximum deformation and overall quality of the shell were determined. The range method was used to analyze sensitivity factors, and the final optimization result that met the minimum deformation and minimum quality was determined. Experimental results show that the rotation error of the main shaft of the rotating mechanism includes axial, radial, and angular motion errors, and experimental value is basically consistent with theoretical value. After the shell optimization, the infrared target pointing errorδ ′ Z = 1.7 1 ′ and the infrared target position offset error ξ ′ = 0.1525 mm meet the accuracy requirements. This method can provide new ideas for precision research and optimization of structural design of rotating mechanism.